Beyond Testing (Classic Edition) : Towards a Theory of Educational Assessment. - Gipps, Caroline (Taylor & amp, 2011)
It is an exceptionally thoughtful assessment of assessment, and I am (along with anyone else who broods about education) much in your debt.' Jerome Bruner, personal communication with the author When this award-winning book was originally published in 1994, a review in the TES said: 'Beyond Testing is a refreshingly honest look at the dilemmas facing those who are trying to make educational assessment more supportive of high-quality learning for all pupils and students! It contains powerful and practical messages for assessment developers, policy-makers, teachers and pupils. It exposes the ve.